Effect of Comprehensive Multi-Provider Primary Care Visits in Type 2 Diabetes Management in a Primarily Uninsured, Ethnic Minority Population: The Comprehensive Care Initiative (CCI) Program - Aisha H. Montgomery; Lydia R. Best; Heather Kitzman; Mahbuba Khan; Abdullah Mamun; Anabelia Aguillon; Kirsten Granberry (SAGE Publishing, 2022)
The Comprehensive Care Initiative (CCI) utilized a quasi-experimental design to evaluate the effects of same room, multi-provider primary care visits on the management of type 2 diabetes (T2D). Patients with T2D were invited to enroll in CCI if they had T2D with glycated hemoglobin (HbA1c) >8.0% or T2D with BMI >30. CCI intervention included delivery of comprehensive same room multi-provider visits with a primary care physician, community health worker, pharmacist, dietitian, medical assistant, and licensed social worker at the same appointment. CCI patients were compared with a propensity score matched control group receiving usual care (n = 56, 50 ± 11 years old, 77% female, 41% African American, 95% uninsured). After 6 months, the adjusted average reduction in HbA1c in the CCI group was 0.97% (SE = 0.45) in comparison to 0.05% (SE = 0.20) in the control group ( P  = .04). This pilot study showed promising results in lowering HbA1c in an uninsured, ethnic minority population of T2D patients through delivery of comprehensive multi-provider primary care visits.